Vitrectomy After ocriplasmin for VitreOmacular adhesion Or Macular hole (VAVOOM) study. Issue 9 (9th December 2015) - Greven, Margaret A; Garg, Sunir; Chiu, Bing; Shah, Sumit P; Wolfe, Jeremy; Fine, Howard F; Roth, Daniel B; Robinson, Joshua; Mong, Jacob; Hsu, Jason; Regillo, Carl; Ho, Allen; et al.
Abstract : Background/aims: To describe the results of pars plana vitrectomy (PPV) for persistent symptomatic vitreomacular traction (VMT) with or without macular hole (MH) after intravitreal ocriplasmin injection. Methods: Multicentre retrospective study of eyes that received intravitreal ocriplasmin between January 2013 and January 2014 for symptomatic VMT with or without MH, and then went on to PPV (ocriplasmin-treated group) for persistent pathology, compared with a control group of patients with symptomatic VMT with or without MH who were offered ocriplasmin injection but proceeded directly to PPV (PPV-only group). Intraoperative characteristics, visual acuity (VA) outcomes and spectral-domain optical coherence tomography images were reviewed for the two groups. Primary outcome measure was VA after PPV. Results: 51 eyes of 51 patients underwent PPV after receiving ocriplasmin, and 22 eyes of 22 patients proceeded directly to PPV. Although VA was significantly better at all time points in the PPV-only compared with the ocriplasmin-treated group, at 3 and 6 months after PPV both groups had similar amount of visual improvement. Both groups had similar rates of pathology resolution; 50/51 (98%) eyes in the ocriplasmin group and 22/22 (100%) eyes in the PPV-only group had release of VMT and/or MH closure after PPV. The two groups had similar PPV-related complication rates. Conclusions: Eyes with persistent symptomatic VMT and/or MH have similarly high rates of pathology resolution as well as similar VA gains regardless of whether they received ocriplasmin prior to PPV.